LEGAL ANALYSIS OF BANK OBSERVATION IN INDONESIA THROUGH LAW PATHOLOGY APPROACH CONSTRUCTION - Reka Dewantara (USU Journal of Legal Studies, 2017)
The development of hybrid products in new forms such as financial technology (fintech) and the emergence of business conglomerates of banks and financial institutions in Indonesia to be sociological juridical factors required independent independent institutions to supervise in the field of microprudential and regardless of the central bank of Bank Indonesia. Juridically the formation of Financial Supervisory Auhtority (FSA) in Indonesia, called the Financial Services Authority based on OJK Act number 21 of 2011 is a mandate of Article 34 of Law no. 23 of 1999 concerning Bank Indonesia as amended by Act no. 3 of 2004 which indirectly undermines the independence of Bank Indonesia. This leads to the need for an integrated regulation that supersedes the regulation in the field of supervision of financial institutions, especially the existing banks. The construction of a legal pathology approach for analyzing the development of regulatory and supervisory models of banking institutions in Indonesia was established through comparison with supervisory models in other countries, analyzing typologies of highly regulated banking institutions in Indonesia, regulatory mapping of regulations related to banking supervision with due regard to theoretical implications and practical implications To realize the principle of good banking governance.